Penerapan Metode Self -Regulation untuk Meningkatkan Kemampuan Mengelola Emosi Anak pada Kelompok 4-5 Tahun di TK Cor Jesu Marsudirini Matraman - Kristi Julita Sipayung, Santa; Yuntina, Lily; Suhardjo, Sudi (INTELEKTIUM, 2025)
This qualitative case study aims to describe the application of self-regulation methods to improve the emotional management skills of 4-5-year-old children at Cor Jesu Marsudirini Kindergarten, Matraman. The subjects were three children in Group A who exhibited difficulty controlling their emotions. Data were collected through observation, interviews, and documentation, analyzed using the Miles & Huberman model (reduction, presentation, verification) and source triangulation. The results showed that before the intervention, children easily cried, became angry, or withdrew when losing in games. After implementing strategies such as deep breathing, verbal reinforcement, simple reflection, teacher modeling, storytelling, and role-playing, children were able to express their feelings verbally, calmed themselves more quickly, and were no longer dependent on rewards or winning. The self-regulation method has proven effective in helping early childhood teachers stimulate children's emotional skills from an early age.